Treatment of Recurrent Aphthous Ulceration by Mastic Orabase - Altaei, Tagreed (Journal of Baghdad College of Dentistry, 2017)
Background: Recurrent aphthous ulcer is a chronic inflammatory disease of the oral mucosa. Substance P has activity in the inflammatory response. Transforming growth factor beta (TGF-β) as immune-modulators regulates the immune response and has anti-inflammatory, pro-inflammatory effects. Pistacia lentiscus (mastic) of Anacardiaceae family have pharmacological activities like anti-inflammatory, antioxidant, and used in treatment of wound and repair. The aim of this study is to find the safety and efficacy of a new product mastic orabase; experimentally and clinically. Methods: This research studied two parts: first; experimentally for assessment of mastic orabase effects on rabbit dermal irritation, efficacy of mastic orabase on the induced ulceration, with histopathology of rabbits’ tissues, and safety: therapeutic index and safety factor. Second; clinical efficacy of mastic orabase on the healing of RAU by assessment of ulcer size reduction, inflammation, healing time, pain, saliva substance P and TGF-β levels in RAU patients, and monitoring for any adverse effects or adverse drug reactions. Results: Experimental study of topical mastic orabase treatment showed significant reduction of inflammation and ulcer size, healing time. Safety of mastic orabase was confirmed by no dermal irritation, no toxicity, and wide therapeutic index range. Clinical study showed reduction of inflammation, ulceration, healing in short time, pain was relieved from the first topical dose, and the anti-inflammatory activity of mastic orabase was confirmed by reduction of salivary substance P and TGF-β elevation. Conclusion: Mastic orabase showed dose-dependent efficacy in the treatment of recurrent aphthous ulceration, short healing time. This may be related to effect of mastic orabase on proinflammatory and anti-inflammatory mediators; substance P and TGF-β.